Peran Depo Pemeliharaan Dan Implikasinya Terhadap Ketahanan Alutsista Arhanud (Studi Di Depo Pemeliharaan Sistem Senjata Arhanud Kota Batu Jawa Timur) - Edi Nugraha (Universitas Gadjah Mada, 2022)
ABSTRACT This study aims to analyze the role of Dohar Sista Arhanud in the maintenance of defense equipment and to analyze its implications for resilience of defense equipment. In this study, the theories used are role theory, bureaucratic theory, maintenance theory, readiness theory and resilience theory. This research method is a qualitative research with analytical descriptive approach. Data collection techniques used are interviews, observation, documentation and literature. Analysis of the data used is data categorization, data reduction, data presentation, and drawing conclusions. The results of this study indicate that through the role played by Dohar Sista Arhanud in the maintenance of the main defense equipment, it has implications for increasing the operational readiness of the main defense equipment , increasing the age of use to create resilience of the main defense equipment. In the implementation of defense equipment maintenance, there are obstacles faced by Dohar Sista Arhanud in maintaining the defense equipment including aspects of personnel, infrastructure, budget, organization and duties as well as policy aspects. The defense equipment maintenance activities carried out have implications for the defense of the main defense system, which can be seen through two aspects, namely: (1) operational readiness of the defense equipment and (2) the resilience of the defense equipment after maintenance.